Perspective: How complex in vitro models are addressing the challenges of predicting drug-induced liver injury - Taylor, K.; Ram, R.; Ewart, L.; Goldring, C.; Russomanno, G.; Aithal, G. P.; Kostrzewski, T.; Bauch, C.; Wilkinson, J. M.; Modi, S.; Kenna, J. G.; Bailey, J. (Frontiers in Drug Discovery, 2025)
Predicting which drugs might have the potential to cause drug-induced liver injury (DILI) is highly complex and the current methods, 2D cell-based models and animal tests, are not sensitive enough to prevent some costly failures in clinical trials or to avoid all patient safety concerns for DILI post-market. Animal-based methods are hampered by important species differences in metabolism and adaptive immunity compared to humans and the standard 2D in vitro approaches have limited metabolic functionality and complexity. On 24 April 2023 the Alliance for Human Relevant Science (https://www.humanrelevantscience.org/) hosted a workshop at the Royal Society, London entitled Drug-Induced Liver Injury (DILI): Can Human-Focused Testing Improve Clinical Translation? The conclusion was that complex in vitro models (CIVMs) provide a significant step forward in the safety testing paradigm. This perspective article, written by the participants, builds on those discussions to provide a ‘state of play’ on liver CIVMs with recommendations for how to encourage their greater uptake by the pharmaceutical industry.